Durability assessment of high-performance concrete with SRAs and FLWAs. (March 2015) - Deboodt, Tyler; Fu, Tengfei; Ideker, Jason H.
Abstract: The use of pre-wetted fine lightweight aggregate (FLWA) and shrinkage reducing admixtures (SRAs) have been shown as effective means to reduce deleterious effects of autogenous and in limited studies, drying shrinkage in concrete. However, minimal research has been done on the durability performance of concretes made with these materials. In this study, freeze–thaw resistance, permeability, and restrained drying shrinkage of high-performance concrete (HPC) were determined. Two methods to reduce shrinkage, pre-wetted FLWA and SRAs, were studied. In mixtures containing either shrinkage reducing method, similar freeze thaw performance could be achieved with an adequate air void system when compared to the control mixture. The addition of FLWA and SRAs also reduced the permeability of HPC by 23% according to ASTM C1202. Furthermore, time to cracking in the restrained ring test (ASTM C1581) was prolonged in both shrinkage mitigation techniques.